PENGARUH KUALITAS PRODUK, ONLINE CONSUMER REVIEW, DAN RATING TERHADAP KEPUTUSAN PEMBELIAN MAKEUP SOMETHINC - Tyas Widya Rini (2021)
This study aims to analyze and prove the effect of product quality, online consumer reviews, and online consumer ratings on purchasing decisions of Somethinc's makeup. This research used a quantitative approach. The sampling technique used was purposive sampling with 75 female who bought Somethinc makeup and domiciled in Jakarta. Data collection using a questionnaire through Google forms. The data analysis technique used descriptive and inferential analysis and processed by SmartPLS 3.3.3 software. The results of the study stated: (1) there was a significant effect from product quality on purchase decision of Somethinc's makeup; (2) there was a significant effect from online consumer review on purchase decision of Somethinc's makeup; (3) there was a significant effect from online consumer rating on purchase decision of Somethinc's makeup.